The Exploration of Pesantren - Based Entrepreneurship Development Strategy Through Teleology Approach - Siswanto, Siswanto (UIN Maulana Malik Ibrahim Malang, 2018)
Cultural difference determines the strategies used for entrepreneurship development. Pesantren (Islamic boarding school) as the oldest educational institution in Indonesia has a unique culture. Pesantren-based entrepreneurship development must be equipped with different characteristics of strategy. The purpose of this research is to explore the entrepreneurship development strategy based on the culture of pesantren through teleology approach. The subject of the current research is Pondok Pesantren Sidogiri (PPS) Pasuruan. It employs case study analysis. Interview and observation methods are used to collect the data. The teleology approach is used to understand entrepreneurial strategies under some perspectives which include; the involved subjects, the projected achievements, and the entrepreneurship development strategy based on the culture of pesantren. The results demonstrate the important role of kiai (pesantren leader), santri (students), and alumni in the development of entrepreneurship in Pondok Pesantren Sidogiri. They seek independence for the intention of worship. They practice the value of tabligh (transparent) and fathanah (professional) for institutional management called Koperasi Syariah (sharia cooperative). In addition, the administrative managers hold the values of shidiq (honest) and amanah (trustworthy). In conclusion, the strategy of pesantren-based entrepreneurship development has typical characteristics of pesantren. Perbedaan budaya menentukan perbedaan strategi pengembangan wirausaha. Pesantren sebagai lembaga pendidikan tertua di Indonesia memiliki budaya yang unik. Pengembangan wirausaha berbasis budaya pesantren tentunya memiliki karakteristik strategi yang berbeda. Tujuan penelitian ini untuk mengeksplorasi strategi pengembangan wirausaha berbasis budaya pesantren melalui pendekatan teleologi. Situs penelitian di Pondok Pesantren Sidogiri (PPS) Pasuruan. Penelitian ini menggunakan analisis studi kasus. Metode wawancara dan observasi digunakan untuk mengumpulkan data yang akan dianalisis. Pendekatan teleologi berguna untuk memahami strategi wirausaha berdasarkan perspektif yang meliputi; subyek yang terlibat, prestasi yang diproyeksikan, dan strategi pengembangan wirausaha berbasis budaya pesantren. Hasil penelitian menunjukkan peran penting kiai, santri, dan alumni dalam pengembangan wirausaha di Pondok Pesantren Sidogiri. Kemandirian untuk niat ibadah menjadi prestasi yang diharapkan. Menerapkan nilai-nilai tabligh (transparansi) dan fathanah (profesional) sebagai strategi pengelolaan lembaga yang berbentuk koperasi syariah. Disamping itu, untuk pengelola dibudayakan nilai-nilai shiddiq (kejujuran) dan amanah (dapat dipercaya). Strategi pengembangan wirausaha berbasis budaya pesantren ini memang memiliki karakteristik yang khas pesantren.